Pendidikan Karakter Prilaku Sosial Anak Usia Sekolah Dasar dalam Keluarga di Kecamatan Banjarmasin Timur - Taufiqurrahman Taufiqurrahman (Universitas Islam Negeri Antasari Banjarmasin, 2017)
Family Education Pattern in Guiding Social Child Behavior on Student’ Parents of Elementary School at Banjarmasin Timur Kota Banjarmasin. Child education a familyas the first education is a basic for parent to lay foundation of personality forming andthe child social behavior, cultivation and introduction to religion and social behavior and and the basic friend ship of children. In this case, the children are necessary to be guided, must be given advices, example, motivation, habit, supervation, and development of conducive education atmosphere which help the children deviloping their social behavior, attitude, knowledge and skill in order to be able socialization of ghildren in their envioronment. Doe to the socialization of children in their family extremely determines to the success in the socialization to the wider environment. In this case, the parents in the family should have a pattern to guide in the child social behavior by applying leadership attitudes democratically based on the development of childrens characters. Keyword: family education pattern, child characters social behavior